A CLINICAL CASE: DIAGNOSTICS OF SHERESHEVSKY TERNER SYNDROME WITH MULTIPLE CONGENITAL ANOMALIES IN MAIN ARTERIES OF A 4 YEAR OLD CHILD, SUFFERING FROM ARTERIAL HYPERTENSION - A.N. Tsygin; A.N. Sikachev; N.N. Kartamysheva; E.N. Tsygina; Z.P. Sharnova; O.B. Kondakova; N.V. Zhurkova ("Paediatrician" Publishers LLC, 2007)
The article provides a substantiation for the differential diagnostics of the symptomatic arterial hypertension of a 4 year old child, suffering from the arterial hypertension of the presumably renoparenchymal origin. In the course of the clinical examination, the researchers found out coarctation of aorta and hypoplasia of the right renal artery as a part of Shereshevsky-Terner syndrome.Key words: arterial hypertension, Shereshevsky-Terner syndrome, coarctation of aorta, renovascular hypertension.